©‌™•£ ¤œ•£

download ©‌™•£ ¤œ•£

of 64

  • date post

    22-Oct-2014
  • Category

    Documents

  • view

    145
  • download

    0

Embed Size (px)

Transcript of ©‌™•£ ¤œ•£

3: - 1.* x2 + y2 = ( > 0) . 2.*x2+y2+x+y=0,0 . 3.* (1, - 1) (- 1, 1) : (x - 1)2 + (y + 1)2 = 8. 4.* x2 + y2 + (x + y + 1) = 0 . 5.* (2,2) 4 (x - )2 + 4 (y - )2 = 1 . 6.* x2 + y2 + 2x + 3y - 1 = 0 x2 + y2 + 2x + 3y +2= 0 . 7.* x2 + y2 = 4 2 y = x. 8.** (x - 1)2 + (y + 2)2 = 1 (x - 2)2 + (y + 1)2 = 10 9.* (x + 1)2 + y2 = 18 y = x + 1. 10.** (- 2, 2) (4, 2) (x - 1)2 + (y - 2)2 = 9 . 11.* x2 + (y - 1)2 = 3 x2 + (y - 1)2 = 310 . 12.* (x + y)2 - 4 = 2 xy . 13.* x = y = , [0, 2) C: x2 + y2 = 2. 13014.* x2 + y2 = 1 1 x + y = 1. 15.* x2 - 2x + 1 + y2 = 5 (1, 0). 16.*x2+y2=2 . 17.*y= 2 2 x - (- x ). 18.**y=x. (x - )2 + (y - ) 2 = 2. 19.* (x1, y1) (x0, y0) . : (x1 - x0)2 + (y1 - y0)2 < 2. 20.** (1, 0) p = 2. 21.*y=3 y2 = 16x. 22.* xy y2 = 2px yy . 23.* xx x2 = 8y. 24.x2=2py 1 (x1, y1) yy1 = p (x + x1). 25.**. . 26.*yy x2 = 2y. 27.*(0,0) y = - 2p, xx. 28.*y2=8x x = - 2 (4, 0). 29.**y2=2pxp>0,(0,0), 131 . 30.* y2 = 3x x = - 43. 31.* x2 = 4y y = - 1. 32.**(x-1)2+y2=1y2=-2x . 33.* x2 = y y = x. 34.*(x0,y0)y2=2px = 0yp (y0 0). 35.*x2+y2=1 y2 = 4x. 36.*y=x ,x0, . yx0 37.*, . 38.*0, . 39.* 22x + 22y = 1 > . 40.** . 21. 41.* , . 42.* 32 x2 + 51 y2 = 23 . 13243.*(,), (- , - ). 44.* , . 45.* . 46.* (2, - 2) C: 25x2 + 9y2 = 1. 47.* x2 + y2 = 1 > 0. 48.* x2 + 2y2 = 1 x2 + y2 = 1 . 49.** 2x2 + y2 = 1 3x2 + 5y2 = 1. 50.* y = - 3 2x2 + 9y2 = 1. 51.* x = 2 2x2 + 3y2 = 1. 52.* . 53.* 22x + 22y = 1 (, ) () x + () y = 1. 54.* 4x2 + y2 = 4 = 33 2. 55.** 9x2 + 4y2 = 1 36x2 + 16y2 = 1 . 56.* 22x- 22y=1. 133 > . 57.* C: 22x - 22y = 1 yy . 58.*, . 59.*x2-y2=2 = 2 . 60.* 22y - 22x = 1 1: y = x 2: y = - x. 61.* x2 - 9y = 0 . 62.* . 63.**(5,4) 16x2 - 25y2 = 40. 64.* . 65.* . 66.*x2+y2=0 , R. 67.* 5x2 - 4y2 = 1 yy (0, 2) (0, - 2). 68.** 3x2- 5y2=1 x2 + y2 = 4. 13469.* y = 21 x 4x2 - y2 = 1. 70.* xOy x2 - y2 = 4 . 71.** 22x - 22y = 1 22y - 22x = 1. 72.*R,(,1) 2x2 - 4y2 = 1. 73.** 3x2- 2y2=1x2- 4y2=1 . 135 1.* (- 2, 3) . x = 3. x = - 2. x2 + y2 = 1 . (x + 2) 2 + (x - 3) 2 = 1. y2 = - 2x 2.* (1, -3) (7, 5), . (4, 4). (3, 4). (4, - 4). (4, 1). (4, - 1) 3.* x2 + y2 = 8 . 2 . 2 2 . 4 2 . 4. 8 4.* x2 + y2 - 6x + 4y + 10 = 0 . (3, - 2). (2, - 3). (2, 3). (- 2, 3). (- 3, 2) 5.*(-1,-1) (4, - 3), . x2 + y2 = 29. (x - 1)2 + (y - 1)2 =29. (x + 1)2 + (y + 1)2 =29 . (x - 1)2 + (y - 1)2 = 29 . (x + 1)2 + (y + 1)2 = 29 6.*(3,9)9, . x2 + y2 = 81. x2 + y2 = 3. x2 + y2 = 9 . (x - 3)2 + y2 = 81. (x - 3)2 + y2 = 49 1367.** (1, 2) xx, . (x - 1)2 + (y - 2)2 = 2. (x - 2)2 + (y - 1)2 = 2 . (x - 1)2 + (y - 2)2 = 4. (x + 1)2 + (y + 2)2 = 2 . (x + 1)2 + (y + 2)2 = 4 8. ** x2 + y2 = 5 (2, 1) . x - 2y + 1 = 0. 2x + 3y + 7 = 0. x + 2y = 4 . 4x + 2y + 1 = 0. y = x 9.** (x - 3)2 + (y - 2)2 = 2 xx. . 1. 2. 3. 5 . 10.* x2 + y2 - 6x - 8y + 2 - 2 + 1 = 0 . . 4. 3. 2. 1 . 0 11.**(x0,0),yy(x0). . (x - x0)2 + y2 =. x20x2 + y2 = . (x - x20x0)2 + y2 = 2 . (x - )2 + y2 = . (x - x0)2 + y2 = x0 12.**(x-)2+(y-)2=2(,,) Ox, Oy, . = . = . > . = = . 13713.** (x - )2 + (y - )2 = 2 . (, ). ( , ) . y = x + 1 . y = - x . xx yy 14.**C1:(x-)2+y2=2C2: x2 + (y - )2 = 2( 0). . 2 . 2 . 22 . C1 C2 . C2 C1 15.** x2 + y2 + Ax + By + = 0 , . 2 + 2 - 4 .+ 0 . 2 + 2 > 4. 42 + 42 - < 0 . 2 + 2 < 4 16.** x2 + y2 + x = 0 . xx . yy . yy . . 17. ** x2 + y2 - 2 (x + y) = - 2, > 0 . (, ). (2, ). (2, 2) . (, - 2). (2, ) 13818.** (21 , 21 ), R x2 + y2 = 1.. , R. , (0, ). . . 19.** (- 1, - 2) (2, 2), . (x + 1)2 + (y + 2)2 = 4. x2 + y2 + 2x + 2y = - 3 . (x - 1)2 + (y - 2)2 = 25. x2 + y2 - 2x - 4y = 3 . (x + 1)2 + (y + 2)2 = 25 20. ** . x2 + y2 = 2 . x2 + y2 = 4 . y = 2 x - 4 . x = 2y - 4 . (x - 2)2 + (y + 2)2 = 4 yx0 -2 2 21. ** x2 + y2 = 5 (- 1, 2). . 2x - y = 5. - x - 2y = 5. x + 2y - 5 = 0 . x - 2y + 5 = 0 . 2x + y = 5 22.**x2+y2=3(+ 2 ,-1). . -2 x + y - 3 = 0 .2 x - y - 3 = 0. x - y = 3 .2 x + y = 3 . - x +2 y = 3 13923. ** (0, 4) (0, 0), . y2 = 8x. y2 = - 8x. y2 = 16x . x2 = 16y. x2 = 8y 24. ** y2 = 16x (1, 4) . y = x . y = - x. y = 2x + 1. y = x + 2. 4y = x 25.* y2 = 8x x - y = 0 . (0, 0) (1, 1). (8, 8) (2, 1). (0, 0) (8, 8) . (1,8 ) (- 1,8 ). (2, 4) (4, 2) 26.** (, 4) y2 = 8x. xx . (4, 4). (- 4, 4). (2, 4). (2, - 4). (2, - 2) 27.**(0,0)x= 23. . y2 = 6x. y2 = - 6x. y2 = 3x. x2 = - 6y. x2 = - 3y 28.** y = x2, 0 . y2 = 2px p = 2 . y2 = 2px p = 2 . . x2 = 2py p = 2 . yy 14029.** y2 = 4x . , > 0 . , = 21 p(p > 0) . 0 . . 30.** y2 = x x2 = y ( 0) . . (0, 0) . . . 31. * y2 = 2px (x1, y1) (0, 0) . = 1yp. = 1y2p. = py1 . = 2py1. = 2p 32. ** y2 = 2px (x1, y1) (x1, - y1). . . yy . xx . 14133.** y2 = 16 x. . . , x > 0 . , x < 0 . 34.**(2,4)y2=8x . 2. 4. 8. 16.8 35.* , 2 , . () - () = . () + () = . () = (). () + () = 2. () - () = 2 36. ** 925x2 + 4y2 = 1 . 67. 1011. 511. 25. 34 37.** (0, - 2) (0, 2) 10, . 29x2 + 25y2 = 1. 4x2 + 5y2 = 1. 2x2 + 4y2 = 1 . 25x2 + 29y2 = 1. 2x2 - 2y2 = 10 38.**yy , 6 142. 25x2 + 16y2 = 1. 3x2 + 5y2 = 1. 5x2 + 3y2 = 1 . 6x2 + 8y2 = 1. 16x2 + 25y2 = 1 39.*C: 22x+ 22y=12 2. . > > . 2 = 2 - 2. 0 < < . > . < 40.** C: 223x + 225y = 1, . 4x2 + 3y2 = 1. 224x + 223y = 1. 4y2 + 3x2 = 1 . 224y + 223x = 1. 2234x + 2254y = 1 41.* 2x2 + 3y2 = 1 . (2, 3) . (0,2 ). ( 3 , 0). (- 1, 0). (0, -1) 42.** 22x + 22y = 1 22x + 22y = 1 . . . . . 43.** 2x2 + 2y2 = 22, 0 . 143. . . , . , = 44.** 4x2 + y2 = 1 . 4x2 + 3y2 = 1. 5x2 + 2y2 = 1. 16x2 + 9y2 = 1 . 16x2 + 4y2 = 1. 2x2 + y2 = 1 45. ** (- 2, 0) (2, 0) . 5x2 + 1y2 = 1. 9x2 + y2 = 1 . 4x2 + 2y2 = 1 . 16x2 + 9y2 = 1. 2x2 + 5y2 = 1 46.**C: 5x2+ 3y2=1(-5 ,0). M .5 y - 5 = 0. + 5 x + 5 = 0.5 x - 15 = 0 . - 5 x + y - 15 = 0.3 5 x - 15 = 0 14447.**C: 2x2+y2=2( 2 ,-1). M . x -2 y = 4.2 x - 2y - 4 = 0.2 x + 2y = 4 . x - 2y - 4 = 0. -2 x - 2y = 4 48.* 16x2 - 25y2 = 400 . y = 45 x. y = 54 x. y = 2516 x . y = 1625 x. 49.**2=8 34 . 4x2 - 3y2 = 1. 9x2 - 7y2 = 1. 9x2 + 3y2 = 1 . 7x2 - 9y2 = 1. 16x2 - 9y2 = 1 50.** C: 224x - 223y = 1. . C yy . y = 34 x . (- 5, 0), (5, 0) . = 3 = 4 . (- 3, 0), (3, 0) 14551.**C1:2x2-2y2=22C2:2y2-2x2=22() . . . . . 52.** C1: 22x - 22y = 1 C2: 22x + 22y = 1 . . . . C2 C1

. 53.** 22x- 22y=11(x1,y1). 1 . 221x - 221y = 1. 21xx - 21yy = 1. 2x1x - 2y1y = 22 . 2x1x - 2y1y = 1. xx1 - yy1 = 1 54.** x2 + y2 = , , 0 . = 1. . < 0 . < 0 .

. = = 55.** 22x - 22y = 1 22x - 22y = - 1 ( ) . . . . . 14656.**f(x)= 31144 x 6 12 (x 3 x - 3) . = 12 . = 3 = 4 . (- 5, 0), (5, 0) . (- 5, 0), (5, 0) . x = - 45 57.** (x, y) :) BM ( ) (AM = 6 (- 5, 0) (5, 0) . 9x2 + 25y2 = 1. 9x2 - 25y2 = 1. 16x2 - 9y2 = 1. 9x2 - 5y2 = 1. 9x2 - 16y2 = 1 58. * x2 - y2 = 3 (- 2, 1). M . x - 2y = 3 . 2x + y = 3. - 2x + y = 3 . 2x + y + 3 = 0. 2x - y + 3 = 0 59. * 2y2 - x2 = 1 (1, 2). M . x + y + 1 = 0. 2x - y = 2. x - 2y + 2 = 0 . 2x - y = - 2. x - y + 1 = 0 147 1.**() , (). (x0, y0). () (x0, y0) 1.x2 + y2 = 1 (0, 1) 2.(x - 2)2 + (y - 1)2 = 1 (2, 0) 3.x2 + y2 = 25 (3, 4) 4.x2 + (y + 2)2 = 5(1, 2) .y = 0 .x + 4 (y + 2) = 5 .y = 1 .y = x .3x + 4y = 25 .x - 2y = 1 () 1234 1482. ** () , (). () - 1.x2 + y2 -= 0 > 0 2.x2 + y2 - 2x + 2y = - 2 3.(x + )2 + (y - )2 = 2x + 22, 0 4.2x2 + 2y2 + 4x - 6y = - 2 . (, 1) = 2 . (- 1, 23) = 23 . (0, 0) = 4 . (, ) = . (1, - ) = 1 . (0, ) = () 1234 1493. ** () , (). () 1.y2 = px 2.x2 = py 3.y2 = - 2px 4.y2 = 2p x .(- 2p, 0) .(8p, 0) .(4p, 0) .(0, 2p) .(0, 4p) .(0, - 2p) () 1234 1504. ** y2 = 2x. () , (). () 1.(0, 0) 2.(21, 1) 3.(21, - 1) 4.(2, 2) .y = x + 21 . yy .- 2y = x + 2 .y = x - 2 .- y = x + 21 .2y = x + 2 () 1234 1515.**() , ., (). () - 1. (- 2, 0) : x - 2 = 0 2. (0, 4) : y + 4 = 0 3. (3, 0) : x + 3 = 0 .x2 = 16y .y2 = - 8x .y2 = 8x .y2 = 12x .x2 = - 16y () 123 1526. ** , . , (). () 1.y2 = x 2.y2 = - 4x 3.x2 = 20y . (- 1, 0) : x + 1 = 0 . (41, 0) : x + 41 = 0 . (- 5, 1) : x + 1 = 0 . (- 1, 0) : x - 1 = 0 . (0, 5) : y + 5 = 0 () 123 1537.**() , (). () - - 1. 240yx 2.-10yxE (-2,0) E(2,0) 3. 20yx-34. 0yxE E-4AE +AE=10 5. 0yxy=4x=2 ) 5x2 + 9y2 = 1 ) 4x2 + 16y2 = 1 ) 16x2 + 4y2 = 1 ) x2 + 5y2 = 5 ) x2 + 2y2 = 1 ) 25x2 + 9y2 = 1 () 12345 1548.**() ., (). () 1. 2. 3. 4. . x + y = 1 . x2 + y2 = 0 . x2 = 9 - (y - 1)2 . 9x2 = 63 + 7y2 . y2 - 16x = 0 . 4x2 = 100 - 25y2

() 1234 1559. ** () , (). () 1. 3x2 - 4y2 = 1 2. 2y2 - 3x2 = 1 3. 6x2 - 5y2 = 30 4. x2 - y2 = 4 . y = x . y = 36x . y = 2x . y = 33 2x . y = 56 5.x . y